PENGEMBANGAN BAHAN AJAR BERBASIS KOMIK DIGITAL PADA MATERI KEANEKARAGAMAN HAYATI DI DAERAHKU KELAS IV SD - Nur Wira Triana; Robenhart Tamba (Universitas Negeri Medan, 2023)
Development of Digital Comic-Based Teaching Materials on Biodiversity Materials in My Area Grade IV Elementary School. The purpose of the research was to produce digital comic-based teaching materials on biodiversity materials in my area that are feasible, practical, and effective. This study used R&D with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model with the research subject of 30 students and grade IV teachers of SDN 105268 Telaga Sari. Data collection techniques use observation, tests, questionnaires, and documentation. The results of the study resulted in feasibility with an average percentage of 95% in the